All You Need Is Fats—for Seizure Control: Using Amoeba to Advance Epilepsy Research - Warren, Eleanor C.; Walker, Matthew C.; Williams, Robin S. B. (Frontiers in Cellular Neuroscience, 2018)
Since the original report of seizure control through starvation in the 1920’s, the ketogenic diet has been considered an energy-related therapy. The diet was assumed to be functioning through the effect of reduced carbohydrate intake regulating cellular energy state, thus giving rise to seizure control. From this assumption, the generation of ketones during starvation provided an attractive mechanism for this altered energy state; however, many years of research has sought and largely failed to correlate seizure control and ketone levels. Due to this focus on ketones, few studies have examined a role for free fatty acids, as metabolic intermediates between the triglycerides provided in the diet and ketones, in seizure control. Recent discoveries have now suggested that the medium chain fats, delivered through the medium chain triglyceride (MCT) ketogenic diet, may provide a key therapeutic mechanism of the diet in seizure control. Here we describe an unusual pathway leading to this discovery, beginning with the use of a tractable non-animal model - Dictyostelium, through to the demonstration that medium chain fats play a direct role in seizure control, and finally the identification of a mechanism of action of these fats and related congeners leading to reduced neural excitability and seizure control.